Genocias ir rezistencija Nr. 30(2) - Buchaveckas, Stanislovas; Rukšėnas, Alfredas; Pocius, Mindaugas; Banionis, Juozas; Okuličiūtė, Lina; Bukaitė, Vilma; Kareniauskaitė, Monika (Genocidas ir rezistencija, 2011)
Pilnas leidinys